Far-field optical nanothermometry using individual sub-50 nm upconverting nanoparticles. Issue 22 (24th May 2016) - Kilbane, Jacob D.; Chan, Emory M.; Monachon, Christian; Borys, Nicholas J.; Levy, Elizabeth S.; Pickel, Andrea D.; Urban, Jeffrey J.; Schuck, P. James; Dames, Chris
Abstract : Temperature measurement of a single, photoluminescent NaYF4 :ErYb nanoparticle, smaller than 50 nm, using only far-field optics. Abstract : We demonstrate far-field optical thermometry using individual NaYF4 nanoparticles doped with 2% Er 3+ and 20% Yb 3+ . Isolated 20 × 20 × 40 nm 3 particles were identified using only far-field optical imaging, confirmed by subsequent scanning electron microscopy. The luminescence thermometry response for five such single particles was characterized for temperatures from 300 K to 400 K. A standard Arrhenius model widely used for larger particles can still be accurately applied to these sub-50 nm particles, with good particle-to-particle uniformity (response coefficients exhibited standard deviations below 5%). With its spatial resolution on the order of 50 nm when imaging a single particle, far below the diffraction limit, this technique has potential applications for both fundamental thermal measurements and nanoscale metrology in industrial applications.